Efektifitas Komunikasi Interpersonal Secara Online Terhadap Contextual Performance Pengurus BEM Universitas X di Era Pandemi Covid-19 : Nicola Fonseca, Mira Sekar Arumi - Fonseca, Nicola; Sekar Arumi, Mira (SOCIAL PHILANTHROPIC, 2024)
This study aims to determine whether or not there is a relationship between the effectiveness of online interpersonal communication on the Contextual performance of BEM Management at Bhayangkara University, Greater Jakarta during the Covid-19 Pandemic Era. The sample technique used is random sampling with a sample of 209 subjects. The results showed that the correlation coefficient was 0.721** and p = 0.000 (p<0.05). This shows that there is a significant positive relationship. The relationship between the two variables is a positive relationship, so it can be said that the Interpersonal Communication of members of the executive organization at Bhayangkara University Jakarta Raya will also have high Contextual performance, and conversely low communication between members of the organization at Bhayangkara University Jakarta Raya, Contextual performance will also be low.